Regarding the numerical solutions of the Sharma-Tasso-Olver equation - Sulaiman, Tukur Abdulkadir; Yokus, Asif; Gulluoglu, Nesrin; Baskonus, Haci Mehmet (E D P Sciences, 2018)
With aid of the Wolfram Mathematica package. this study investigates the solutions of a nonlinear model with strong nonlinearity, namely: the Sharma-Tasso-Olver equation. We use the improved Bernoulli sub-equation function method in acquiring the analytical solution to this equation. we successfully obtain one-singular soliton solution with exponential function structure. Through the obtained analytical solution. the finite forward difference method is used in approximating the exact and numerical solutions to this equation. We check the stability of the finite forward difference method with this equation using the Fourier-Von Neumann stability analysis. We find the L-2 and Lo., norm error to the numerical approximation. We present the interesting 3D and 2D figures of the obtained singular soliton solution. We also plot the graphics of the numerical error. exact and numerical approximations data obtained in this study by using the MATLAB package.
3rd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 04-06, 2018 -- Final Int Univ, Girne, CYPRUS
Keywords: Variational Iteration Method